Digital Marketing Berbasis AI untuk Peningkatan Daya Saing UMKM Kuliner di Kabupaten Kampar - Mardiana Putri; Zulfikar Zulfikar; Doli Apriansyah (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
Culinary MSMEs are among the fastest-growing subsectors of the creative economy in Indonesia, including in Kampar Regency. However, most of them still face challenges in competitiveness, particularly in terms of limited digital literacy, marketing strategies, and technology adoption. This study aims to analyze the application of Artificial Intelligence (AI)-based digital marketing in enhancing the competitiveness of culinary MSMEs in Kampar. A mixed-methods approach was employed, combining quantitative surveys of 50 culinary MSMEs and qualitative in-depth interviews with business owners. The findings reveal that AI-driven digital marketing contributes to improving promotional effectiveness, personalized content, consumer trend analysis, and product distribution efficiency. Nevertheless, AI adoption remains limited to basic chatbots and sales analytics, with major barriers including investment costs, low digital literacy, and limited ecosystem support. These results highlight the importance of collaboration between government, academia, and industry in strengthening the digital capacity of culinary MSMEs to compete in both local and global markets